Gallop toward the sun : Tecumseh and William Henry Harrison's struggle for the destiny of a nation - Stark, Peter, 1954- (Random House, an imprint of Penguin Random House LLC, 2023)
"The conquest of indigenous land in the American East through corrupt treaties and genocidal violence laid the groundwork for the conquest of the American West. Acclaimed author Peter Stark exposes the fundamental conflicts at play through the little-known but consequential struggle between two extraordinary leaders. William Henry Harrison was born to a prominent Virginia family, son of one of the signers of the Declaration of Independence. He journeyed west, became governor of vast Indiana Territory and sought statehood by attracting settlers and imposing one-sided treaties. Tecumseh belonged to an honored line of Shawnee warriors and chiefs. His father died while fighting the Virginians flooding into Kentucky and in his dying words, extracted a promise from his sons to "Never give in" to the land-hungry Americans. Tecumseh was, by all accounts, one of the nineteenth century's greatest leaders. An eloquent speaker, he traveled from Minnesota to Florida and west to the Great Plains convincing far flung tribes to join a great confederacy and face down their common, American, enemy. Eager to stop U.S. expansion, the British backed Tecumseh's confederacy in a series of battles during the forgotten western front of the War of 1812 that would determine control of the North American continent"--